Ideologi dan Epistemologi Kitab Tuḥfat al-Râghibîn Karya Muhammad Arshad al-Banjari - M. Rusydi (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2014)
Tuhfat al-Râghibîn is the first book of theology for Banjarese besides the book of Usûl al-Dîn. This book focuses not on the area of surface-structure (outer aspects) but particularly on the deep-structure area (inner aspects). The deep-structure study will help interpret the meaning of the book in its relation to the historical, social, and political context. This paper will explore the deep-structure area which consists of two problems, namely the ideology and the epistemology of Tuhfat al-Râghibîn. This study concludes that the ideology of the book is Sunn?, and the epistemology of the book is bayânî. It is based on an analysis that the source of the book is text (nass), its method is qiyâs and ijtihâd, and the rational argument in the book is used as a means of justification, although it still maintains a balance between revelation and rationalism. In addition, the type of argument is defensive-apologetic, the validity of its argument is the conformity of text to the reality, while the basic principle is infisâl (discontinuance) and tajwîz (permissiveness).